Nanoclay-Doped Electrospun Nanofibers for Tissue Engineering: Investigation on the Structural Modifications in Physiological Environment - Miele D; Ruggeri M; Vigani B; Viseras C; Natali F; Del Favero E; Rossi S; Sandri G (International Journal of Nanomedicine, 2023)
Dalila Miele,1 Marco Ruggeri,1 Barbara Vigani,1 Cesar Viseras,2 Francesca Natali,3 Elena Del Favero,4 Silvia Rossi,1 Giuseppina Sandri1 1Department of Drug Sciences, University of Pavia, Pavia, Italy; 2Department of Pharmacy and Pharmaceutical Technology, School of Pharmacy, University of Granada, Granada, Spain; 3Institut Laue-Langevin, Grenoble, France; 4Department of Medical Biotechnology and Translational Medicine, University of Milano, Segrate Milano, ItalyCorrespondence: Giuseppina Sandri, Tel +390382987728, Email giuseppina.sandri@unipv.itBackground: Clay minerals are nanomaterials that have recently been recognized as enabling excipients that can promote cell adhesion, proliferation, and differentiation. When nanoclays are loaded in a 3D polymeric nanostructure, the cell–substrate interaction is enhanced, and other bioactive properties are optimized.Purpose: In this study, hectorite (HEC)- and montmorillonite (MMT)-doped polymeric scaffolds were explored for the treatment of deep and chronic skin lesions.Methods: Scaffolds were manufactured by means of electrospinning and then crosslinked by heating. Physicochemical analyses were correlated with in vitro biopharmaceutical characterization to predict the in vivo fate of the clay-doped scaffolds.Results and Discussion: The addition of MMT or HEC to the polymeric scaffold framework modifies the surface arrangement and, consequently, the potential of the scaffolds to interact with biological proteins. The presence of nanoclays alters the nanofiber morphology and size, and MMT doping increases wettability and protein adhesion. This has an impact on fibroblast behavior in a shorter time since scaffold stiffness facilitates cell adhesion and cell proliferation.Conclusion: MMT proved to perform better than HEC, and this could be related to its higher hydrophilicity and protein adhesion. Keywords: nanomaterials, montmorillonite, hectorite, chitosan, nanofibers, electrospinning, tissue engineering